Diagnosis and management of connective tissue disease‐associated interstitial lung disease in Australia and New Zealand: A position statement from the Thoracic Society of Australia and New Zealand*. Issue 1 (24th November 2020) - Jee, Adelle S.; Sheehy, Robert; Hopkins, Peter; Corte, Tamera J.; Grainge, Christopher; Troy, Lauren K.; Symons, Karen; Spencer, Lissa M.; Reynolds, Paul N.; Chapman, Sally; de Boer, Sally; Reddy, Taryn; et al.
ABSTRACT: Pulmonary complications in CTD are common and can involve the interstitium, airways, pleura and pulmonary vasculature. ILD can occur in all CTD (CTD‐ILD), and may vary from limited, non‐progressive lung involvement, to fulminant, life‐threatening disease. Given the potential for major adverse outcomes in CTD‐ILD, accurate diagnosis, assessment and careful consideration of therapeutic intervention are a priority. Limited data are available to guide management decisions in CTD‐ILD. Autoimmune‐mediated pulmonary inflammation is considered a key pathobiological pathway in these disorders, and immunosuppressive therapy is generally regarded the cornerstone of treatment for severe and/or progressive CTD‐ILD. However, the natural history of CTD‐ILD in individual patients can be difficult to predict, and deciding who to treat, when and with what agent can be challenging. Establishing realistic therapeutic goals from both the patient and clinician perspective requires considerable expertise. The document aims to provide a framework for clinicians to aid in the assessment and management of ILD in the major CTD. A suggested approach to diagnosis and monitoring of CTD‐ILD and, where available, evidence‐based, disease‐specific approaches to treatment have been provided.